Gonadal Maturity of Commercial Species of Stichopus Vastus Sea Cucumber (Holothuriidea : Sthichopodidae) in Karimunjawa Waters, Jepara Districs, Central Java - Sulardiono, Bambang (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
Sea cucumber resources is one of the commodities of marine resources is very important and has a highcommercial value. One of the commercial sea cucumber species found in the waters of the Stichopus vastus Karimunjawa (local name: gamets). The high commercial value sea cucumbers cause excessive exploitation of the resources, so that would threaten its sustainability. To preserve water resources in the sea cucumber can be maintained properly required for resource management actions. Aspects of reproduction is one aspect of the basis used to determine the management of aquatic resources in sea cucumbers Karimunjawa, which is associated with survival and breeding. Research purposes (1) to analyze and determine the development level of gonad maturity in the waters of Stichopus vastus Karimunjawa, (2) analyze and know the stage of mature gonads S. vastus monthly in Karimunjawa waters, (3) analyze and determine the condition of mature gonads S. vastus based on length of interval scales in the waters Karimuinjawa, and (4) identify and analyze the gonadal somatic index (GS I) when mature gonads S.vastus in Karimunjawa waters. Sample collection on a monthly basis during the period July 2010 until May 2011, within methods of systematic sampling. Samples were collected from the catch freely on a predetermined location within the boundaries of the study sites. Pickling sea cucumbers sample with 2.5% Mg Cl2 use traditional and gonad used for solution of buffered formalin. During the study found that the mature gonad stage is the stage of development that has the highest percentage compared to the stages of gonad maturity of the other. Every month observation, always get ripe gonad condition, with the percentage varying, so that seasonal patterns are less likely. Obtained information that the S. vastus spawn in the month - the month September- November and March to May, with a length of 269-286 mm size range. Quantitative assessment based on the gonad somatic index (GSI) found that in July and September in a condition to cook, while in other months, namely November, January, March, and May show the condition begins to mature. Keywords : Stichopus vastus, gonad maturity, and gonad somatic index